1970
DOI: 10.3329/bjsir.v46i3.9038
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Compounds from the Rihzomes of <i>Sansevieria hyacinthoides</i>

Abstract: Three known compounds were isolated from the n-hexane extract of the rihzomes of Sansevieria hyacinthoides, they were two steriods; β-sitosterol (1) and daucosterol (2), and a flavonoid; isokaemferide (3). The structures of the compounds were elucidated on the basis of NMR spectral analysis as well as comparison with available data in the literature. All extracts and the three pure compounds were evaluated for their antimicrobial activity. The compounds showed moderate activity against Bacillus subtilis, Stapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…A large proportion of the World population depends on the traditional medicine because of the shortage and high expenses of orthodox medicine (Dutta and Maharia, 2012;Li et al, 2011;Sultana et al, 2011). Natural products play a central role in the development of novel drug for the treatment and prevention of diseases (Khan et al, 2015;Sharma et al, 2015;Yu et al, 2013;Dhanamani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of the World population depends on the traditional medicine because of the shortage and high expenses of orthodox medicine (Dutta and Maharia, 2012;Li et al, 2011;Sultana et al, 2011). Natural products play a central role in the development of novel drug for the treatment and prevention of diseases (Khan et al, 2015;Sharma et al, 2015;Yu et al, 2013;Dhanamani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gamboa-Angulo et al [100] identified steroids 25S-ruscogenin and 1β,3β-dihydroxy-5,16-pregnadien-20-one from the leaves of S. hyacinthoides while Khare [8] identified alkaloids aconitic acid and Sansevieria from the leaves and roots of the species (Table 2). Sultana et al [25] identified a flavonoid isokaemferide and steroids β-sitosterol and daucosterol from the rhizomes of S. hyacinthoides (Table 2). Van Wyk et al [31] argued that the value of S. hyacinthoides in treating hemorrhoids is due to the presence of various sapogenins, particularly 25S-ruscogenin.…”
Section: Phytochemical Composition Of S Hyacinthoidesmentioning
confidence: 99%
“…S. hyacinthoides is native to east, central, and southern Africa, but the species has been introduced to several other countries as an ornamental and fiber crop [18,22]. In Bangladesh and South Africa, S. hyacinthoides is grown in home gardens as an ornamental, medicinal, and spiritual plant [23][24][25][26][27][28]. The leaves and roots of S. hyacinthoides are marketed as herbal medicines in the Eastern Cape and KwaZulu-Natal provinces in South Africa [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial Screening: Antimicrobial activities of all extracts (methanol, n-hexane, ethyl acetate and n-butanol) of the roots of H. indicus were carried out by the disc diffusion methods 12,13 . Five bacterial species which include two Gram-positive and three Gram-negative bacterial strains and two fungus Aspergillus niger and Aspergillus flavus were taken for the test.…”
Section: Extraction and Isolationmentioning
confidence: 99%